DARI YAHUDI KE ISLAM : Pergulatan Muhammad Asad dengan Al-Qur’an dan Perenungan Makna Wasaṭiyyah - Ahmad Nabil Amir; Tasnim Abdul Rahman (AL ITQAN: Jurnal Studi Al-Qur'an, 2025)
The article aims to analyses the spiritual impression of Muhammad Asad (1900-1992) with his Western-secular Jews background, in relation with the Qur’an as highlighted in his magnum opus The Message to the Qur’an and its commentary The Meditation as well as in his 23 days physical journey from Tayma to Mecca, leading to his discovery of Islam as alluded to in his remarkable autobiography, The Road to Mecca. The research explores the extent of its spiritual impression on his consciousness of metaphysical ideas and tawhidic worldview. The book reflected his Arabian journey travelling across sand desert of Iran, Syria, Turkey as well as the Nufud and Rubu‘ al-Khali (the Empty Desert) of Arabian Peninsula. It depicted an enduring value he found in the Arab people and the ideal of Islam he learned from its people. The paper employed descriptive-qualitative method  with content analysis approach. It analyzed the text of The Road to Mecca and the Message of the Qur’an using interpretative and historiographical approach to identify its essence and basic premise. The finding shows that the book illustrates his emotional and spiritual quest for truth depicted through his experience in the landscape of Arabia that resonates with his consciousness of Islamic identity and belief, informing its spiritual and religious outlook of life. The book reminisces of his past profiling his accomplishment in integrating sacred meaning of religion into practical term of life.